2009
DOI: 10.1109/tnsre.2009.2023294
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Neuromuscular Electrical Stimulation Tracking Control of a Human Limb

Abstract: Abstract-A high-level objective of neuromuscular electrical stimulation (NMES) is to enable a person to achieve some functional task. Towards this goal, the objective of the current effort is to develop a NMES controller to produce a knee position trajectory that will enable a human shank to track any continuous desired trajectory (or constant setpoint). A nonlinear control method is developed to control the human quadriceps femoris muscle undergoing nonisometric contractions. The developed controller does not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 131 publications
(77 citation statements)
references
References 32 publications
0
77
0
Order By: Relevance
“…If the delay in muscle response causes any problems, feedforward control has to be implemented with the closed-loop control. Although another study showed good tracking control performance [11], it used total knee-joint dynamics model at the sitting position and the disturbance included in the model is considered to significantly affect on practical application such as FES cycling.…”
Section: Discussionmentioning
confidence: 99%
“…If the delay in muscle response causes any problems, feedforward control has to be implemented with the closed-loop control. Although another study showed good tracking control performance [11], it used total knee-joint dynamics model at the sitting position and the disturbance included in the model is considered to significantly affect on practical application such as FES cycling.…”
Section: Discussionmentioning
confidence: 99%
“…A computer was used to collect data from the encoders and execute a closed-loop RISE (robust integral of the sign of the error) controller. 13 The RISE controller calculates the voltage required at any given time for a subject's knee joint/shank to follow a given desired trajectory. The desired trajectory was selected as a sinusoid ranging from 5 to 35 with a period of 1.5 seconds.…”
Section: Methodsmentioning
confidence: 99%
“…Leg angle was controlled using the closed-loop nonlinear control strategy 13 to adjust the voltage (i.e., amplitude modulation). To reduce the effect of day-to-day variability in muscle response to stimulation, the control gains were adjusted to minimize the baseline tracking error.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…NMES artificially contracts muscle groups by applying external stimulation current. Closed-loop control of NMES can be used to generate advanced functional tasks (in this case NMES is also called functional electrical stimulation (FES)) such as walking [2,3], single leg extension [4][5][6][7][8][9], and upper extremity grasping and reaching [10][11][12].…”
Section: List Of Tablesmentioning
confidence: 99%